Society and fake news: The global crisis of systematic disinformation in brazilian education - Júnior, Tarcísio Bezerra de Lima (Seven Editora, 2023)
The study aims to problematize the dissemination  of fake news, counterinformation and disinformation in the school environment as well as their impact on the socio-educational formation of Brazilian students in the final years of high school. Globalization and the facilitation of technological access to virtual media platforms have given rise to a new space of communication and entertainment today. Cyberculture has accelerated and "democratized", in a way, the producers of media content, but it has "weakened" information security and popularized systematic disinformation. The research is structured on events that occurred in the school environment (public and private schools) in relation to the dissemination of fake news and disinformation. The data will be collected and tabulated through the qualitative-quantitative approach and will offer subsidies to the research problem. The analysis of the results points to the generalization of disinformation and the practice of informational villainy, as well as presents a social stratification of the impact of  fake news in the school environment, pointing to the  public school relatively as more conscious, but more vulnerable to the dispersion of fake news. DOI:https://doi.org/10.56238/sevened2023.006-073